2020
DOI: 10.1136/bmjopen-2019-035889
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of HIV infection among college students in Nanjing, China: a cross-sectional survey

Abstract: ObjectiveThis study aimed to investigate the epidemiological characteristics and HIV/AIDS-related knowledge, attitudes and practice (KAP) among HIV-positive college students.DesignA cross-sectional study.SettingFive districts of Nanjing, China.ParticipantsA total of 156 college students with newly diagnosed HIV infection between September 2015 and July 2017.Main outcome measuresSocial-demographic characteristics, mode of HIV acquisition, infection of sexually transmitted diseases, risky sexual behaviours and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…There may be two reasons for the increase in the proportion of students with HIV/AIDS over the study period. First, homosexual intercourse has been the main mode of transmission among HIV-infected students, as in other provinces in China [ 16 , 22 ]. Surveys conducted in Liaoning, Beijing and Hefei showed HIV prevalence rates of 1.7–3.0% among MSM students, i.e., up to 50 times higher than that in the general Chinese population (0.057%) [ 23 – 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There may be two reasons for the increase in the proportion of students with HIV/AIDS over the study period. First, homosexual intercourse has been the main mode of transmission among HIV-infected students, as in other provinces in China [ 16 , 22 ]. Surveys conducted in Liaoning, Beijing and Hefei showed HIV prevalence rates of 1.7–3.0% among MSM students, i.e., up to 50 times higher than that in the general Chinese population (0.057%) [ 23 – 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, a national report, showed that homosexual transmission accounted for 26% of all new cases of HIV, and among students, 82% were homosexually transmitted [ 13 ]. In one study in students from Nanjing, 95% of 156 positive HIV tests were from MSM [ 50 ]. There is a clear need for appropriate sexual and reproductive health services for MSM.…”
Section: Discussionmentioning
confidence: 99%
“…So the rate of 85.6%is lower than the rate required by the national health authority on the awareness rate of AIDS prevention knowledge among college students 95% [23]. It suggests we need to further strengthen the AIDS knowledge education especially for the freshmen when they were enrolled in the colleges [24].…”
Section: Discussionmentioning
confidence: 99%